Preparation and Properties of 2, 6‐Diamino‐3, 5‐dinitropyrazine‐1‐oxide based Nanocomposites. Issue 2 (11th February 2013) - An, Chongwei; Li, Hequn; Geng, Xiaoheng; Li, Junlong; Wang, Jingyu
Abstract With estane as binder, a new nanocomposite energetic material based on 2, 6‐diamino‐3, 5‐dinitropyrazine‐1‐oxide (LLM‐105) was successfully prepared by the spray drying method. Scanning Electron Microscope (SEM), Transmission Electron Microscope (TEM), and X‐ray diffraction (XRD) was employed to characterize the nanocomposite samples. The impact sensitivity and thermal decomposition properties of the nanocomposites were also measured and analyzed. The results show that the nanocomposite particles are spherical in shape and range from 1 μm to 10 μm in size. The composite is aggregated of many tiny granules with nucleus/shell structure, in which the shell thickness and crystal size of LLM‐105 are about 20 nm and 50–100 nm. The crystal type of LLM‐105 in the nanocomposite is similar to that of raw LLM‐105, however, the diffraction peaks become weaker and wider mainly due to decreasing of particle size. The nanocomposite has lower impact sensitivity and better thermal stability.